Cross-cultural communication of the Indonesian students in China - Uspal Jandevi; Mahwash Zareen (International Journal of Communication and Society, 2020)
This paper aims to find out how the process and the steps taken by Indonesian students studying in China to overcome culture shock during their study in China. This research seeks to provide answers to cultural shock events that arise from a process of cross-cultural communication. The data were obtained by conducting an in-depth interview process and then processed optimally using the Speech Codes Theory (SCT) initiated by Gerry Philipsen. This study shows that Indonesian students tend to cope with cultural shock events from cross-cultural communication processes when mingling with other community members.